2022
DOI: 10.1002/mde.3681
|View full text |Cite
|
Sign up to set email alerts
|

How agglomeration affects alliance governance and innovation performance: The role of cluster size

Abstract: We investigate how the size of the geographic cluster in which a firm is located influences its governance choice between equity and non-equity alliances and subsequent innovation performance. We argue that firms located in larger clusters tend to form non-equity alliances rather than equity alliances because the communication and control benefits of cluster membership, which increase with cluster size, reduce in-cluster firms' need to form equity alliances. We also claim that the effect of this preferential u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 105 publications
0
9
0
Order By: Relevance
“…At the same time, ref. [68] found a positive relationship between cluster size and alliance governance. Scholars reported that alliance governance moderated the influence of local clusters on a firm's innovation-related performances.…”
Section: Strategic Management and Firm Performancementioning
confidence: 91%
See 1 more Smart Citation
“…At the same time, ref. [68] found a positive relationship between cluster size and alliance governance. Scholars reported that alliance governance moderated the influence of local clusters on a firm's innovation-related performances.…”
Section: Strategic Management and Firm Performancementioning
confidence: 91%
“…Despite the rising interest in studying local clusters and the high enthusiasm with which business managers and local authorities embraced these new advancements, there is also some contradictory evidence regarding the positive effect of local clusters on firm performance. For instance, while some studies reported a positive and strong effect of local clusters on firm performance [10,68,70], other researchers found only a weak intensity effect for the same relationship [12,29]. Other studies even reported contradictory evidence [14].…”
Section: Strategic Management and Firm Performancementioning
confidence: 99%
“…Prior studies on economic geography have emphasised that geographic proximity strengthens externalities from partners located near one another (Capaldo & Petruzzelli, 2014; Kwon et al, 2022; Ryu et al, 2023). Specifically, first, when working with nearby partners, firms can increase face‐to‐face interactions.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…In this context, firms can utilise their geographic proximity to socially dominant partners to increase (or decrease) the benefits (or costs) of collaborations. The literature on economic geography has already explored how geographic proximity affects firms' innovation outcomes (Bignami et al, 2019; Feldman & Florida, 1994; Presutti et al, 2019; Ryu et al, 2023). Moreover, prior studies have noted the positive effects of firms having geographic proximity to their inter‐organisational partners because it encourages knowledge sharing (Capaldo & Petruzzelli, 2014; Parrino, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Cluster firms are those organizations in a cluster. In industrial clusters, multiple linkages and geographic proximity are two fundamental characteristics [3] Establishing both vertical and horizontal links with other firms and associated institutions geographically localized [4] brings various benefits to all members in an industrial cluster, such as agglomeration economies, improved productivity, better knowledge sharing and collaborative innovation, and can better adapt to a more complex and turbulent technological environment [5][6][7][8][9][10]. Such advantages of clusters are especially salient and critical for firms in strategic emerging industries (SEIs).…”
Section: Introductionmentioning
confidence: 99%